Are M&As spurring or stifling innovation? Evidence from antidiabetic drug development - Jan Malek; Jo Seldeslachts; Reinhilde Veugelers (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This paper provides empirical evidence on which M&A deals spur innovation, and which stifle it. To do so, we consider not only the product market position of the acquiring firm, but also the position of both target and acquirer in the technology space. Focusing on the antidiabetic drugs market, our dataset tracks the lifecycle and patenting of all individual antidiabetic projects in development between 1997 and 2017. We show that most terminations of acquired projects occur while the projects are still far from product market entry. Nevertheless, a number of these early-stage acquisitions have a positive impact on innovation. These cases arise when incumbents acquire projects close to their own projects in product markets, but only if these projects are also close in technology markets. Those deals are associated with increased subsequent patenting, which is consistent with the exploitation of technological synergies. Our results point to the crucial role of combining both product market and technology market positions in assessing the innovation effects of pharmaceutical M&As.
Keywords: L41; L65; O31; 330; M&As; innovation; R&D; pharmaceutics; technology; novelty; patents